PERFORMA PERTUMBUHAN UDANG WINDU (Penaeus monodon) YANG DIBUDIDAYAKAN BERSAMA KERANG HIJAU (Perna viridis) DENGAN SISTEM IMTA - Sri Rejeki; Restiana Wisnu Aryati; Chlara Evania (Departemen Akuakultur FPIK UNDIP, 2018)
ABSTRACT Integrated Multi-Tropic Aquaculture (IMTA) is a cultivation system in which organic waste from cultivation activities can be utilized by other biota in one container so as to reduce the environmental impact of cultivation activities. Organic waste can be utilized as the growth of phytoplankton which will be used other biota as natural food. This research is focused on the species of tiger shrimp (P. monodon) as the main cultivated commodity, while the green mussels (P. viridis) is one of the biota that can utilize the phytoplankton that flourish because of organic waste in the waters. The purpose of the study is to determine the effect of green mussel stock density on the growth and survival rate of tiger shrimp with IMTA system. The tiger shrimp used were stadia postlarvae (PL30) with size 0.11 - 0.14 gram /shrimp. The stocking density is 80 tiger shrimps per container with 1m2 container size. This study used a complete randomized design study (RAL) with 5 treatments and 3 replications. The stocking density of the green mussel being used as treatment are 0, 30, 45, 60, and 70 green mussels per container. The results showed that the average growth rate of tiger shrimp in treatment A (with stocking density of 0 green mussels) was 22,06±0,18%/day, treatment B (with stocking density of 30 green mussels) was 28.89±0.20%/day, treatment C (with stocking density of 45 green mussels) was 27.09±0.20%/day, treatment D (with stocking density of 60 green mussels) was 25.32±0.21%/day and treatment E (with stocking density of 75 green mussels) was 23.92±0.12%/day. The average value of tiger shrimp survival rate on B was 80.00%, A was 78.33%, C was 77.92%, D was 74.58% and E was 61.25%. The best green mussels stocking density for tiger shrimp growth and survival rate is with stocking density of 30 green mussels (treatment B). Keyword: Growth, Survival Rate, Green Mussel, Tiger Shrimp, IMTA